Going minimal: An exploration of reduction as a design method - Bramasta Putra Redyantanu (Department of Architecture Faculty of Engineering Universitas Indonesia, 2021)
The purpose of this paper is to reflectively explore minimalist architecture as an architecture that is driven by the reduction-based design method. The discussion aims to reframe the design processes and methods of minimalist architecture as informed by field observation. The phenomenon of applying a minimalist architectural approach has become a trend in small-scale housing in Indonesia lately. In the country, the small-scale residential design processes take place in different contexts and are faced with various limitations, from resources, budgets, land size, materials, and so on. The study will frame this discussion around exploring the reductive design method as a way of responding to these limitations. Informed by design strategies from the modern architecture movement, the study was conducted by observing reduction strategies in eight small-scale domestic design which was published and well-narrated in various media. The study findings demonstrate that the reduction does not only exist in the visual aspect of the design and construction process. It also exist in numerous other design elements, such as materials, forms, spaces, and ornamentation, as a strategic response towards the limitations of various resources.